Patients' perceptions of healthcare professionalism-a Romanian experience - Daniela Popa; Daniela Druguș; Florin Leașu; Doina Azoicăi; Angela Repanovici; Liliana Marcela Rogozea (BMC, 2017)
Abstract Background The main objective of this cross sectional study was to assess the psychometric properties of a new research instrument. The secondary aim was to analyze patients' levels of dissatisfaction with the professionalism of medical staff. Methods A social survey questionnaire was created and administered online. The instrument consisted of two scales: the 30-item patient dissatisfaction scale and the 10 items institutional scale. In this article, we assessed only the patient dissatisfaction scale. The research population includes 1838 subjects. The statistical procedures used were descriptive statistics, Pearson's correlation, and factorial analyses with the SPSS.19 software. The internal consistency of the instrument was determined using the Cronbach's alpha coefficient. We used a principal component analysis to investigate the factorial validity of the scale. Results The patients' scale of dissatisfaction obtained an alpha Cronbach score of 0.81. Three latent factors corresponding to three dimensions of dissatisfaction emerged from the data: medical staff's ability to communicate, medical staff's hygiene, as well as sanitary and privacy conditions within the hospital. The first factor explained 43.47% of the variance in patient dissatisfaction, the second factor explained 10.24%, and the third factor explained 7.59%; overall, the three factors explained 61.30% of the total variance. Conclusion The Romanian healthcare system has an organization and management structure which has shown few changes since the communist period. Our study indicates that although more than 25 years have passed since the political regime changed in Romania and the introduction of a different system of social care, there have been no corresponding changes in the medical staff's mentality or in the way that patients are approached. The present assessment of patient dissatisfaction is not a strictly theoretical exercise; it also represents a valuable instrument for healthcare system management.